(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
An Internal Quality Assurance Cell that exists on paper, meets once before a NAAC peer team arrives, and goes quiet for the remaining four years and eleven months of the accreditation cycle is not a quality mechanism — it is a filing system. Across a large share of Indian universities and colleges, this is precisely what the IQAC has become, and the gap between what it is mandated to do and what it actually does represents one of the most consequential governance failures in Indian higher education today. This study examines that gap through the lens of Total Quality Management, a management philosophy whose defining claim is that quality cannot be inspected into an organisation at periodic intervals but must be built into the everyday processes and working culture of the institution itself. The investigation was carried out across fourteen NAAC-accredited universities in Uttar Pradesh between January and June 2025, combining structured questionnaire surveys administered to 1,140 faculty members and administrative staff with in-depth institutional documentation analysis covering IQAC minutes, Annual Quality Assurance Reports, feedback data, and accreditation-period correspondence. The purpose was not to measure quality outputs — NAAC grades do that, imperfectly — but to examine the quality processes and governance behaviours that produce or fail to produce those outputs on a continuous basis. Findings reveal that TQM's five functional dimensions — leadership commitment to quality, process standardisation through the Plan-Do-Check-Act cycle, stakeholder feedback integration, data-driven institutional decision-making, and the cultivation of an organisation-wide quality culture — are either partially implemented or entirely absent in eleven of the fourteen institutions studied. Only three institutions demonstrated functioning quality governance systems that operated with any consistency outside the accreditation window. The study develops a TQM-anchored operational model adapted to the specific regulatory architecture of Indian higher education, maps it against NAAC criteria and NEP 2020 reform requirements, identifies the institutional and systemic barriers that make sustained implementation difficult, and proposes a phased transition pathway that accounts for the resource and governance realities of Indian universities rather than assuming conditions that do not exist.